THE RELATIONSHIP BETWEEN MATHEMATICAL PROBLEM SOLVING ABILITY AND STUDENTS' MATHEMATICAL LITERACY ABILITY IN SOCIAL ARITHMETIC - Elsa Dwi Herawati; Hanifah Nurus Sopiany (Universitas Muhammadiyah Metro, 2026)
This study aims to analyze the relationship between mathematical problem-solving ability and mathematical literacy ability of eighth-grade students in junior high school on the topic of social arithmetic. The research uses a quantitative approach with a correlational method. The population of the study consists of all eighth-grade students in a junior high school in Karawang. The sample was selected using a simple random sampling technique with the Slovin formula, resulting in 100 students from a total population of 480 students. The research instrument consisted of essay tests with three questions to measure mathematical problem-solving ability and three questions to assess mathematical literacy ability. The analysis steps included normality testing, correlation testing, significance testing (t-test), and calculating the coefficient of determination to assess the contribution or effect of mathematical problem-solving ability on mathematical literacy ability. The results of the study show that there is a significant relationship between mathematical problem-solving ability and mathematical literacy ability of eighth-grade students in junior high school on the topic of social arithmetic, with a moderate level of relationship. Furthermore, mathematical problem-solving ability has an influence of 30.92% on mathematical literacy ability.